2001
DOI: 10.1007/s004390100462
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CC chemokine receptor 5 (CCR5) delta-32 polymorphism in inflammatory bowel disease

Abstract: The inflammatory bowel diseases (IBD) Crohn's disease (CD) and ulcerative colitis (UC) are complex multifactorial traits involving both environmental and genetic factors. Recent studies have shown the important role of pro-inflammatory cytokines and chemokines, including RANTES, in IBD. RANTES is the natural ligand for the CC-chemokine receptor 5 (CCR5). The chromosomal location of the CCR5 gene on 3p21 coincides with an IBD-susceptibility locus identified by genome-wide scanning. A 32-bp deletion (A32) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
(12 reference statements)
0
25
1
2
Order By: Relevance
“…However, it is unlikely that the CCR5Δ32 allele is an important marker for predisposition to IBD 74,75 .…”
Section: Other Diseasesmentioning
confidence: 99%
“…However, it is unlikely that the CCR5Δ32 allele is an important marker for predisposition to IBD 74,75 .…”
Section: Other Diseasesmentioning
confidence: 99%
“…One study found a significant association between CCR5-D32 homozygosity and perianal CD. 29 There were no associations with disease susceptibility or other clinical features of IBD, and none of these studies included PSC patients. [30][31][32][33][34] PSC patients have been included in two studies appearing in abstract form only.…”
Section: Introductionmentioning
confidence: 98%
“…The CCR5 gene has also been associated with both diseases [5,6], Significant associations have been demonstrated between both a functional CARD15 SNP (2104T, haplotype 4) and a synonymous CARD15 SNP (1761G, haplotype 1), and severe pulmonary sarcoidosis phenotypes. An association between the CCR5 HHC haplotype and chest radiographic stage IV disease has been established.…”
Section: Discussionmentioning
confidence: 99%
“…There are associations between phenotypic variability and human leukocyte antigen class II alleles in both sarcoidosis (DQB1*0201 with Lofgren's syndrome and erythema nodosum [1]; DQB1*0602 with severe pulmonary disease [1,2]) and Crohn's disease (DRB1*07 with ileal involvement [3]; DRB1*0103 with extraintestinal manifestations [4]). Furthermore, the HHC haplotype of the C-C chemokine receptor (CCR)5 gene (which promotes T-cell recruitment and activation) is a marker for parenchymal involvement [5] but not for sarcoidosis overall, whereas the 32 bp deletion (D32) polymorphism of CCR5 is associated with the subgroup of Crohn's patients with perianal disease [6].…”
mentioning
confidence: 99%